Dependence of proficiency at competitions on body build, physical ability, volleyball technical and psychophysiological tests in young female volleyballers (aged 13-16 years) - Stamm, R.; Stamm, M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Relying on literature (Thissen-Milder, Mayhew, 1991) and our experience of work as coaches, we tried to reveal to which extent the proficiency in volleyball depend on 4 basic - the players` technical skills, physical fitness, psychophysiological abilities and anthropometric characteristics. Methods The sample consisted of 46 female volleyball players aged 13-16 years, who were healthy, had trainings at least 3 times a week and had trained at least 3 years. The complex of volleyball technical tests consisted of two overhead pass tests, one forearm pass test, two spike tests, one feint test, two serve tests and the reception test. By the help of physical fitness tests (n=9) the players` jumping ability, maximum aerobic endurance, trunk strength, flexibility, deftness and speed of movement, upper body and arms strength were assessed. The girls` psychophysiological characteristics were established using a corresponding computer program (Thomson, 1992) (21 tests), which assessed the reaction time to auditory and visual stimuli, the perception of the speed of a moving object. In order to compare individually the speed of processing different information the additional test of anticipatory reflection of reality was carried out. The methodology of the anthropometric study contained measuring of 50 anthropometric variables (the method of Martin) and 11 skinfolds. The performance of game elements was measured empirically during championship games using the original computer program "Game" in 32 volleyballers. Results The proficiency of performing volleyball elements - serve, reception, feint, block and attack was calculated by regression models from the 14 anthropometric measurements, 4 physical fitness, 5 volleyball technical and 7 psychophysiological test results, which showed significant correlation with proficiency in the game. As a result, we found out that the anthropometric factor was significant in the performance of all the game elements, being most essential (71-83%) for attack, block and feint. Good results in physical ability tests granted success in reception (44%) feint (18%) and attack (22%). Volleyball technical tests were important in reception (39%) and in feint (44%). Psychophysiological tests determined the efficiency in four elements and were very essential for block (98%) and attack (80%) which are usually performed in the greatest deficit of time. Discussion Our results confirmed that volleyball proficiency depends on players` different abilities. The anthropometric characteristics are significant and more attention should be paid to the development of psychophysiological abilities in the future.